Things fall away : Philippine historical experience and the makings of globalization - Tadiar, Neferti Xina M. (Neferti Xina Maca), 1964- (Post-contemporary interventions., 2009)
An argument that subaltern experiences that are devalued and overlooked in progressive late-twentieth-century Philippine literature have been essential to the social and economic changes wrought by globalization.